(untitled) (Nigerian Journal of Technology, 2005)
Environmental and economic analysis was performed on the wastes from Air Liquid Nigeria Ltd. The company’s waste water, spent oil, noise and air pollutants were examined. Results show no serious adverse impact on the ambient air quality. There was serious noise pollution problem around the factory hall and generator areas. Results of the waste-water analysis revealed that the company is not responsible for the pollution of Oginigba River as the parameters analyzed were well below FEPA standards. Spent oil analysis showed that about 97.5% of what the company disposes off as waste constitutes potentially utilizable products such as gasoline (12.3%), kerosene (20.2%) and gas oil (64.8%) were obtained by recycling the spent lubricants by the process of table distillation. These were of comparable quality with the corresponding standard products in the market. However, the recycled products had a little more impurities, but the levels of purity can be improved by better recycling. A detailed cost - Benefit analysis carried out between disposal and recycling revealed that the latter is a viable option.